Immunocytochemistry Improving the Diagnosis of Trichomonas vaginalis Infections. (23rd March 2017) - Fonseca, Thaisa Helena S.; Oliveira, Fabrício M. Silva; Alacoque, Marina; Rocha, Marcella Israel; Leite, Henrique Vitor; Santos, Joseph F. Guimarães; Busatti, Haendel G. N. O.; Caliari, Marcelo Vidigal; Gomes, Maria Aparecida
Abstract : The aim of this study was to evaluate the immunocytochemistry (ICC) to diagnose trichomoniasis, particularly asymptomatic infections. By culture serial dilutions, ICC was able to detect 1 trophozoite/mL, while the culture was positive up to 100 trophozoites/mL. The ICC in vivo detection capability was assessed in vaginal secretions of mice experimentally infected and in vaginal swabs from asymptomatic HIV-positive pregnant women compared with culture. All vaginal secretion samples from mice were positive according to both methods. Swabs from fifty-five asymptomatic women were positive in four (7.27%) of them by culture. Beyond these four, another ten (25.45%) women were positive by immunocytochemistry, proving their higher sensitivity (p = 0.002 ), noticing 3.5 times more positives. ICC had better performance in both successive dilutions as in asymptomatic women, showing higher sensitivity and specificity. In this way, its facility of execution and cost-effectiveness support its practicality, as a routine procedure to diagnose trichomoniasis not only when the parasite load is lower but probably in all clinical scenarios.